Hepatic steatosis in response to acute alcohol exposure in zebrafish requires sterol regulatory element binding protein activation - Passeri, Michael J.; Cinaroglu, Ayca; Gao, Chuan; Sadler, Kirsten C. (Hepatology (Baltimore, Md.), 2009)
Steatosis is the most common consequence of acute alcohol abuse and may predispose to more severe hepatic disease. Increased lipogenesis driven by the sterol response element binding protein (SREBP) transcription factors is essential for steatosis associated with chronic alcohol ingestion, but the mechanisms underlying steatosis following acute alcohol exposure are unknown. Zebrafish larvae represent an attractive vertebrate model for studying alcoholic liver disease (ALD), because they possess the pathways to metabolize alcohol, the liver is mature by 4 days post‐fertilization (dpf), and alcohol can be simply added to their water. Exposing 4 dpf zebrafish larvae to 2% ethanol (EtOH) for 32 hours achieves ∼80 mM intracellular EtOH and up‐regulation of hepatic cyp2e1, sod, and bip, indicating that EtOH is metabolized and provokes oxidant stress. EtOH‐treated larvae develop hepatomegaly and steatosis accompanied by changes in the expression of genes required for hepatic lipid metabolism. Based on the importance of SREBPs in chronic ALD, we explored the role of Srebps in this model of acute ALD. Srebp activation was prevented in gonzo larvae, which harbor a mutation in the membrane‐bound transcription factor protease 1 (mbtps1) gene, and in embryos injected with a morpholino to knock down Srebp cleavage activating protein (scap). Both gonzo mutants and scap morphants were resistant to steatosis in response to 2% EtOH, and the expression of many Srebp target genes are down‐regulated in gonzo mutant livers. Conclusion: Zebrafish larvae develop signs of acute ALD, including steatosis. Srebp activation is required for steatosis in this model. The tractability of zebrafish genetics provides a valuable tool for dissecting the molecular pathogenesis of acute ALD. (HEPATOLOGY 2008.)